Design and Build a Research Information System at National Cyber and Crypto Polythecnic with Recommender System for Thesis Supervisor Based on Text Similarity Metric - Wijayanti, Rheva Anindya; Hanaputra , Rayhan Ramdhany; Setiawan, Hermawan; Girinoto; Yasa , Ray Novita; Lumbantoruan, Jacob; Firmansyah , Muhammad Lucky Aulia (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2025)
Politeknik Siber dan Sandi Negara (Poltek SSN) currently does not have an adequate system for managing research proposals. As a university, it must fulfill the Tri Dharma of Higher Education, one of them is research. Therefore, it is necessary to build a proposal for a management information system. Several previous studies have shown that research information systems can be built with several web frameworks. The approach of utilizing web scraping technology can integrate Google Scholar research data into the information system and recommendation services for accompanying lecturers using the Text Similarity Metric method to provide relevant results. In this study, an integrated research information system application will be built with Google Scholar, implementing the Text Similarity Metric method for the recommendation system for accompanying lecturers, and using the CodeIgniter 4 framework. The integration of the system with this lecturer recommendation service will be tested through monitoring lecturer satisfaction related to the research services provided by the system developed. The results obtained in this study are a research system that works in accordance with the business processes at Poltek SSN with the highest accuracy score on the cosine similarity algorithm of 92,95% and user satisfaction test results of 97,76%.